Analisis Manajemen Risiko pada UMKM “DIVINCES” - Widianingsih, Nindri; Setiyani, Shinta; Tri Pratiwi, Meilanie (Universitas Serambi Mekkah, 2024)
This study analyzes risk management in MSMEs at Divinces MSME, a bag-making brand, with a focus on financial, operational, market, and raw material availability risks. Through case studies and surveys, this study reveals that MSMEs generally face difficulties in accessing capital, facing fluctuations in market demand, and are vulnerable to disruptions in raw material supply. This study suggests the development of an integrated risk management system, including risk identification, risk assessment, and formulation of mitigation strategies. In addition, support from the government and financial institutions is needed to improve MSME access to relevant resources and information.